2015
DOI: 10.1111/are.12778
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary microalgae on fatty acids and digestive enzymes in copepodCyclopina kasignete, a potential live food for fish larvae

Abstract: The copepod Cyclopina kasignete is a potential live food in aquaculture and its fatty acid components and digestive enzymes were investigated. Three dry algal products (mixed algae, Melosira sp. and Nannochloropsis oculata) and two fresh microalgae (Tisochrysis lutea and N. oculata) were fed to the copepod for 30 days. The essential fatty acids (EFA) in copepods were altered by feeding different types of dry algae. The copepod fed dry Melosira sp. or fresh T. lutea contained higher eicosapentaenoic acid (EPA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 59 publications
1
18
0
1
Order By: Relevance
“…Some studies have indicated that calanoid copepods generally lack the ability to synthesize long‐chain fatty acids. Conversely, harpacticoid and cyclopoid copepods are reported to be able to synthesize EPA and DHA from dietary short‐chain fatty acids (Desvilettes, Bourdier, & Breton, ; Monroig et al., ; Rasdi et al., ). Both ALA and SDA are commonly considered the precursors of EPA and DHA in fatty acid synthetic pathway of animals (Monroig et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have indicated that calanoid copepods generally lack the ability to synthesize long‐chain fatty acids. Conversely, harpacticoid and cyclopoid copepods are reported to be able to synthesize EPA and DHA from dietary short‐chain fatty acids (Desvilettes, Bourdier, & Breton, ; Monroig et al., ; Rasdi et al., ). Both ALA and SDA are commonly considered the precursors of EPA and DHA in fatty acid synthetic pathway of animals (Monroig et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Selecting a suitable feed is a crucial factor that extensively influences the productivity and quality of copepod cultures (Kleppel, Hazzard, & Burkart, ). Recent studies have focused on the evaluation of a suitable microalgal diet for copepods in captive conditions that belong to orders such as Calanoida (Camus, Zeng, & McKinnon, ; Milione & Zeng, ; Ohs, Chang, Grabe, DiMaggio, & Stenn, ; Pan et al., ), Harpacticoida (Arndt & Sommer, ; Caramujo, Boschker, & Admiraal, ; Pinto, Souza‐Santos, & Santos, ; Rajthilak et al., ) and Cyclopoida (Lee, Park, Lee, & Kang, ; Rasdi, Qin, & Li, ). Different microalgal feed preferences among copepod species may result from several factors such as size and shape suitability, digestibility and the nutritional value of the microalga for copepods.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the relatively higher abundance of PUFA of R. salina cultured in saturated irradiances and in nutrient excess will benefit the performance of copepods. Please note that the nutrient content in copepods, unlike rotifers and Artemia, cannot be manipulated through enrichment techniques due to their avoidance (Huntley et al 1986;Rasdi and Qin 2014;Rasdi et al 2015) and nutrient content in copepods can only be enhanced by feeding on high-quality algae (Rasdi and Qin 2014;Rasdi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The high content of essential fatty acids in fish fed copepod is possibly due to the content of n-3 highly unsaturated fatty acids (n-3 HUFA) in C. kasignete as reported by Rasdi et al (2015). The contents of essential fatty acids, such as EPA, DHA and ARA, in larval fish depended on the composition of live food combination in the rearing tank.…”
Section: Discussionmentioning
confidence: 80%
“…The cyclopoid copepod Cyclopina kasignete has been successfully mass cultured and reported as a potential live food for fish larvae (Rasdi, Qin, & Li, ). Since this copepod contains the essential nutrition needed by fish larvae, it is necessary to test if this copepod species can be effectively ingested by fish larvae.…”
Section: Introductionmentioning
confidence: 99%